2000
DOI: 10.1034/j.1600-0412.2000.079009744.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thrombocytopenia at term: a population‐based study

Abstract: Women with gestational thrombocytopenia do not require alteration of their treatment. Fetal blood sampling is not considered necessary when thrombocytopenia is discovered unexpectedly at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
3
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 16 publications
6
104
3
6
Order By: Relevance
“…The incidence of thrombocytopenia in this study was 11.68%. This figure was higher than figures of 11.6% reported by Boehlen et al in and 7.2% reported by Sainio et al 2,3 The higher prevalence in this study may be because of malaria and dengue infections. The present study found no influence of age and religion on prevalence of thrombocytopenia in pregnancy like Mathews et al 10 From our findings, gestational thrombocytopenia occurred across the three trimesters.…”
Section: Discussioncontrasting
confidence: 68%
“…The incidence of thrombocytopenia in this study was 11.68%. This figure was higher than figures of 11.6% reported by Boehlen et al in and 7.2% reported by Sainio et al 2,3 The higher prevalence in this study may be because of malaria and dengue infections. The present study found no influence of age and religion on prevalence of thrombocytopenia in pregnancy like Mathews et al 10 From our findings, gestational thrombocytopenia occurred across the three trimesters.…”
Section: Discussioncontrasting
confidence: 68%
“…In the present study, incidence of thrombocytopenia during pregnancy was 8.8%. Burrows [2], found thrombocytopenia in 6% and Sainio et al [5] reported a 7.3% prevalence of thrombocytopenia in a population based surveillance study. Thus, the prevalence of thrombocytopenia in Indian population is similar to world literature (5-12%).…”
Section: Discussionmentioning
confidence: 95%
“…Silver [12] & Aster et al [13] reported that mostly GT is detected incidentally and women have no symptoms. Sainio et al [5] reported that cases of GT have no impact on either the mother or the fetus. GT was the most common cause in this study with a platelet count ranging from 65,000 to 135000 ll -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Sejeny in 1975 [6] was the first to report gestational thrombocytopenia in 405 healthy pregnant women using electronic particle counter [6]. Since then, a number of global reports described a sequential reduction of platelet count as pregnancy advances [7][8][9][10][11][12][13][14][15][16][17][18] with a 10-20% fall in platelet count [19]. Frequency of gestational thrombocytopenia was estimated to be 7-12% at term [12,14,15].…”
Section: Quantitative Changes In Plateletsmentioning
confidence: 99%
“…Since then, a number of global reports described a sequential reduction of platelet count as pregnancy advances [7][8][9][10][11][12][13][14][15][16][17][18] with a 10-20% fall in platelet count [19]. Frequency of gestational thrombocytopenia was estimated to be 7-12% at term [12,14,15]. A platelet count of 80 x 10 9 /L is considered to be a safe threshold [20] with no impact on either mother [21] or the fetus [15], unless the thrombocytopenic mother has some comorbids [14].…”
Section: Quantitative Changes In Plateletsmentioning
confidence: 99%